2019
DOI: 10.1007/s11255-019-02074-9
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone alleviates diabetic nephropathy through promoting autophagy in podocytes

Abstract: Purpose Podocytes are terminally differentiated cells lining the Bowman’s capsule. Podocytes are critical for the proper glomerular filtration barrier function. At the same time, autophagy is crucial for maintaining podocyte homeostasis and insufficient autophagy could cause podocyte loss and proteinuria that is commonly observed in diabetic nephropathy (DN). Methods In this study, we investigated the role of spironolactone in podocyte loss and autophagy. DN model was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…In addition, eplerenone was reported to inhibit ADAM17 activity in human monocytes ( Satoh, Ishikawa, Minami, Akatsu, & Nakamura, 2006 ), which should potentially promote cell surface ACE2 activity. In line with this, in a diabetic nephropathy model, improvement of kidney pathology by spironolactone was associated with decreased serum ACE2 levels ( Dong et al, 2019 ).…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, eplerenone was reported to inhibit ADAM17 activity in human monocytes ( Satoh, Ishikawa, Minami, Akatsu, & Nakamura, 2006 ), which should potentially promote cell surface ACE2 activity. In line with this, in a diabetic nephropathy model, improvement of kidney pathology by spironolactone was associated with decreased serum ACE2 levels ( Dong et al, 2019 ).…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 67%
“… Hsu et al (2016) Aliskiren/ Renin antagonist, antihypertensive Female non obese diabetic/ ShiLtJ and NOR/LtJ mice No effect on renal ACE2 activity, but increased ACE2 mRNA expression in kidney. Riera et al (2016) Aliskiren/ Renin antagonist, antihypertensive Male Balb/c mice/ Streptozotocin-induced diabetes model Decreased gingival tissue ACE2 mRNA expression Oliveira et al (2019) Ivabradine/ Pacemaker current inhibitor, Heart failure medication Dogs/ heart failure model Increased cardiac ACE2 activity R. C. Gupta, Want, Rastogi, Zhang, & Sabbah (2012) Spironolactone/ MRB Male Wistar rats/ Aortocaval fistula induced heart failure model Heart failure caused decreased cardiac ACE2 expression and enzyme activity was restored by eprosartan Karram et al (2005) Spironolactone/ MRB Heart failure patients/ Monocyte-derived macrophage Increase in ACE2 activity and ACE2 mRNA expression one-month post therapy Keidar et al (2005) Spironolactone/ MRB Male Sprague-Dawley rats/ Diabetic nephropathy model Decreased plasma ACE2 level Dong et al (2019) Spironolactone/ MRB Male Sprague-Dawley rats/ Obstructive jaundice model Decreased renal ACE2 mRNA expression due to obstructive jaundice was reversed by spironolactone Kong et al (2019) Eplerenone/ MRB Balb/C mice/Heart and kidney Increase in cardiac ACE2 activity and ACE2 mRNA expression, but nonsignificant increase in the kidneys Keidar et al (2005) Eplerenone/ MRB Wistar rats/ Heart Prevented aldosterone induced reduction in cardiac ACE2 mRNA expression Yamamuro et al (2008) Eplerenone/ MRB Dahl salt-sensitive hypertensive rats/ Hypertension model No effect on cardiac ACE2 mRNA and protein expression in hypertensive rats Takeda et al (2007) Eplerenone/ MRB Male Wistar rats/ Uninephrectomy and high salt induced kidney injury model Partial reversal of aldosterone induced decrease of renal ACE2 expression in injured and high salt exposed kidneys. …”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 99%
“…Other antihypertensive and cardiovascular drugs such as dihydropyridines (51)(52)(53), the combination sacubitril-valsartan (54), thiazide diuretics (55) and mineralocorticoid receptor antagonists (56)(57)(58) affected in-vitro ACE2 tissue expression. Regarding beta-blockers, we retrieved a single in-vitro study, reporting no impact of atenolol on aortic tissue expression of ACE2 (59).…”
Section: -Acei-arb and Covid-19mentioning
confidence: 99%
“…Several studies have demonstrated that spironolactone (SP) as a mineralocorticoid antagonist plays an important role in preventing the physiopathology of renal injuries [13,14]. For example, there are several reports showing the beneficial effects of SP in animal models of kidney damage induced by diabetes [15], ischemia [13] and obstructive jaundice [16]. Furthermore, low doses of SP carry advantages to patients with chronic kidney disease [17].…”
Section: Introductionmentioning
confidence: 99%